Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1021/ac102550e
|View full text |Cite
|
Sign up to set email alerts
|

Study of Water Adsorption on Organics Crystal Surfaces Using a Modified X-ray Photoelectron Spectroscopy Instrument

Abstract: The coupling of a high partial pressure water vapor system to a conventional X-ray photoelectron spectroscopy instrument for use with both organic powders and single crystals is described. The modified chamber serves a dual purpose as both a treatment and sample preparation apparatus. The design utilizes the high- and cryo-temperature capabilities of the existing system to allow investigation of various states of surface water, as well as the interplay between temperature, water, and surface structure of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…On the side of experiment, a variety of different tools are used, including surface force apparatus, , optical methods (infrared and Raman spectroscopy, ellipsometry, etc. ), classical methods of surface science such as temperature-programmed desorption (TPD), and so forth, X-ray scattering, ,, neutron scattering, X-ray spectroscopy, and so forth. As far as well-defined organic or biology-relevant surface is required, it is frequently mimicked by molecular self-assembly on a solid support.…”
Section: Introductionmentioning
confidence: 99%
“…On the side of experiment, a variety of different tools are used, including surface force apparatus, , optical methods (infrared and Raman spectroscopy, ellipsometry, etc. ), classical methods of surface science such as temperature-programmed desorption (TPD), and so forth, X-ray scattering, ,, neutron scattering, X-ray spectroscopy, and so forth. As far as well-defined organic or biology-relevant surface is required, it is frequently mimicked by molecular self-assembly on a solid support.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the XPS technique has not been widely applied to drug analysis. However, XPS was successfully used to show the susceptibility of hydrochloride pharmaceutical salts to water-induced dissociation at the surface. , XPS was also critical to characterize the surface chemistry of peptide modified sol–gel thin films. Recently, several studies have indicated the potential of XPS for exploring intermolecular drug–polymer interactions . Of particular interest is the high sensitivity of XPS for the detection of the degree of proton transfer in acid–base systems by measuring the BE shift of the involved atoms. , For example, a strong N 1s shift of +2 eV toward higher BEs has been observed for both the protonation of an aromatic nitrogen in theophylline as well as the protonation of the aliphatic nitrogen in piperidine groups …”
Section: Introductionmentioning
confidence: 99%
“…However, XPS was successfully used to show the susceptibility of hydrochloride pharmaceutical salts to water-induced dissociation at the surface. 22,23 XPS was also critical to characterize the surface chemistry of peptide modified sol−gel thin films. 24−26 Recently, several studies have indicated the potential of XPS for exploring intermolecular drug−polymer interactions.…”
Section: ■ Introductionmentioning
confidence: 99%